Preliminary performance screening of microbial consortia on fusarium basal rot control and shallot growth - Aisyah, Siti Nur; Asih, Kulsum Kurnia; Suseno, Dyah Rahmawati; Setiawan, Aprilia Budhi; Astuti, Agung; Hidayat, Taufiq; Syafriani, Elly; Harikrishna, Jennifer Ann; Putri, Siska Wahyuni (Universitas Lampung, 2026)
Developing an effective biocontrol consortium requires comprehensive assessment to ensure that the selected microbial combinations can provide both strong disease suppression and plant growth-promoting effects. This study aimed to evaluate the performance of four biocontrol consortia composed of indigenous microbes from Bantul Regency, Indonesia, in suppressing Fusarium basal rot (FBR) and promoting the growth of shallot (Allium cepa var. aggregatum) cv. Bauji. Three indigenous isolates were used: Trichoderma asperellum strain PBt1, Bacillus cereus strain PBt2, and B. cereus strain PBt3. Four consortia were formulated by combining two or three of these isolates, designated as Consortia A, B, C, and D. The biocontrol activity against Fusarium solani DRB-1 was evaluated for both single isolates and consortia. A greenhouse experiment was conducted using a Completely Randomized Design with two inoculation timings (before planting and early vegetative stage) and five replicates. The performance of each consortium was assessed based on FBR severity and shallot growth parameters. Results showed that Consortia B (T. asperellum PBt1 + B. cereus PBt3) applied before planting achieved the highest FBR reduction (34.8%) at 42 days after planting (DAP). Moreover, this consortium significantly enhanced shallot yield, as reflected by increased bulb weight and number. These findings suggest that Consortia B has strong potential to improve both FBR management efficacy and shallot productivity.